Introduction of Alien Tree Species and Its Influence on Floristical Composition and Vegetation Structure of Acidophilous Oak Forests: the Experimental Plots in the Zielonka Forest - Ratyńska, Halina; Grodzki, Marian; Waldon, Barbara; Wachowiak, Ewa (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
In 1879 Schwappach first established 54 experimental forest plots on habitat of acidophilous oak forest Calamagrostio-Quercetum in the Zielonka Forest near Poznań, on which 20 exotic tree species were cultivated. Until this day 32 of the mentioned forest sites have been preserved and today only 9 species are present there. The aim of the study was to determine actual condition of the experimental plots, a description of their flora and vegetation, as well as a comparison with other test plots situated in the direct neighbourhood. Basing on 63 phytosociological relevés, an influence of exotic species plantings on the structure of vegetation and local biodiversity was assessed. Floristic richness of both experimental plots (88 species), as well as their direct neighbourhood (68) was recognised, along with the geographical-historical groups spectrum and species affiliation to phytosociological classes.